2013
DOI: 10.1002/star.201200200
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid microencapsulation by spray‐drying in native and acid‐modified starches from different botanical sources

Abstract: Native starches (NS) of maize (M), potato (P), and rice (R) were subjected to mild acid treatment for producing modified starches (ModSs). NRS and all the ModS were used for microencapsulating ascorbic acid (AA) by spray‐drying. AA retention %, surface AA %, AA stability, particle size analysis, glass transition‐water activity behavior and morphology of the microcapsules were studied. NRS microcapsules resembled “popcorn” balls of starch granules bound together by protein bridging. ModS microcapsules morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…The resulting mixture was homogenized with vortex equipment and immediately fed into the spray‐dryer (Mini Spray Dryer B‐290, BUCHI Corporation, New Castle, DE). The liquid flow rate, and the inlet and outlet air temperatures were maintained at 7 mL min −1 , 160 °C and 110 °C, respectively . Experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting mixture was homogenized with vortex equipment and immediately fed into the spray‐dryer (Mini Spray Dryer B‐290, BUCHI Corporation, New Castle, DE). The liquid flow rate, and the inlet and outlet air temperatures were maintained at 7 mL min −1 , 160 °C and 110 °C, respectively . Experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the use of maltodextrin for the encapsulation of anthocyanins produced protective microcapsules with a slight decrease in the anthocyanins content after 10 weeks . Recent studies have reported the microencapsulation of AA by spray‐drying, using different wall materials either one at a time or in combination . The effects of the wall material on microencapsulation efficiency, stability during storage, controlled release rates, and AA bioavailability were characterized …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthocyanins from Corozo (Bactris guineensis) encapsulated with maltodextrins were largely affected by the environment's humidity (>76%) (Osorio et al, 2010). On the other hand, starches modified by acid hydrolysis have shown good encapsulating properties (Palma-Rodriguez et al, 2013;Spada et al, 2012). For increasing the stability of the encapsulated anthocyanins, it is desirable to have low moisture absorption.…”
Section: Introductionmentioning
confidence: 99%